TILAPIA (OREOCHROMIS NILOTICUS PETERS) TOCINO PROCESSING: TECHNOLOGY TRANSFER - Dalaguit, Mary Ann L. (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 15 No. 1, 2012, 2012)
This aimed to improve the value of fishery products. This discloses that adding value to fish products could improve odour, colour, flavour and texture thus increasing the acceptability of Tilapia Tocino. This experimental research used laboratory technique as basis for technology transfer through entrepreneurial and techno-guide production. The acceptability of the different attributes as perceived by the trained laboratory panels ranges from Slightly Desirable to Desirable in odor and flavor, brown in color, Moderately Tender to Tender in texture. Preference test showed descriptive rating of Like Moderately to Like Very Much. Consumer panelists Prefer Tilapia Fillet Cured in Spices with Kalamansi. The test of significant differences showed Insignificant for odor, color, flavor, texture and general acceptability at 5 % level of confidence. Tilapia tocino cured with spices and kalamansi have Return on Investment of 116 %, earning per peso of investment after deducting cost of materials and production adding 25% mark up price. It is concluded that tilapia meat was acceptable in tocino preparation and recommended adopting the recipe for technology transfer through entrepreneurial/techno-guide production.